Lactoferrin-containing immunocomplex mediates antitumor effects by resetting tumor-associated macrophages to M1 phenotype. Issue 1 (26th March 2020) - Dong, Hongliang; Yang, Yueyao; Gao, Chenhui; Sun, Hehe; Wang, Hongmin; Hong, Chao; Wang, Jun; Gong, Fangyuan; Gao, Xiaoming
Abstract : Background: Tumor-associated macrophages (TAMs) resemble M2-polarized cells with potent immunosuppressive activity and play a pivotal role in tumor growth and progression. Converting TAMs to proinflammatory M1-like phenotype is thus an attractive strategy for antitumor immunotherapy. Methods: A mouse IgG1 (kappa) monoclonal Ab, M-860, specific to human lactoferrin (LTF) was generated by using the traditional hybridoma cell fusion technology. TAMs were generated by culturing human and mouse CD14 + monocytes in tumor-conditioned media containing a cytokine cocktail containing recombinant interleukin-4 (IL-4), interleukin-10 (IL-10) and macrophage colony stimulating factor (M-CSF). TAMs after treatment with immunocomplex (IC) between human LTF and M860 (LTF-IC) were phenotypically and functionally characterized by flow cytometry (FACS), ELISA, Q-PCR and killing assays. The antitumor effects of LTF-IC were further analyzed using in vivo experiments employing tumor-bearing human FcγRIIa-transgenic mouse models. Results: Through coligation of membrane-bound CD14 and FcγRIIa, LTF-IC rendered TAMs not only M2 to M1 conversion, evidenced by increased tumor necrosis factor α production, down-regulated M2-specific markers (CD206, arginase-1 and vascular endothelial growth factor) and upregulated M1-specific markers (CD86 and HLA-DR) expression, but also potent tumoricidal activity in vitro. LTF-IC administration conferred antitumor protective efficacy and prolonged animal survival in FcγRIIa-transgenic mice, accompanied by accumulation of M1-like macrophages as well as significantly reduced infiltration of immunosuppressive myeloid-derived suppressor cells and regulatory T cells in solid tumor tissues. Conclusions: LTF-IC is a promising cancer therapeutic agent capable of converting TAMs into tumoricidal M1-like cells.